Object detection using artificial intelligence - Wang, Tian (Nanyang Technological University, 2022)
Computer vision technology is changing the way people live. One important issue of computer vision is object detection which is the basis for high-level semantic information analysis of images. The objective of the object detection is to detect all items of the predefined classes and provide its localization by bounding boxes. It is a supervised learning problem. Object detection has many applications like face detection, vehicle detection, people counting, security and surveillance and so on. Integrating object detection technology into factory management has many benefits. It could help to monitor safety protection, improve production efficiency, control product quality and so on.